Visualized ultra-mini percutaneous nephrolithotripsy and ureteroscopic soft lithotripsy in remove of 1.5~2.5 cm calculi from the lower calyces: an analysis on efficacy and safety - JIANG Yonghao; LEI Xinghui; ZENG Tiebing; MA Qiang (Di-san junyi daxue xuebao, 2020)
Objective To investigate the safety and efficacy of visual ultra-mini percutaneous nephrolithotripsy(VUMP) and ureteroscopic soft lithotripsy(FURS) in remove of 1.5~2.5 cm calculi from the lower calyces. Methods Clinical data of 116 patients undergoing VUMP and FURS in our hospital from February 2016 to June 2019 were collected and retrospectively analyzed. The patients were divided into VUMP group(n=62) and FURS group(n=54). The general clinical data, operation time, length of hospital stay, short- and long-term(30 d after operation) stone clearance rates, post-operative complications, hemoglobin change in 2 h after operation, and post-operative procalcitonin and C-reactive protein levels and leukocyte count were recorded and analyzed. Results The VUMP group had significantly shorter operation time(37.25± 8.39 vs 49.52±10.57 min, P < 0.05) and lower postoperative white blood cell count [(11.05±2.43)×109/L vs(13.57±2.71)×109/L], P < 0.05), but more obvious postoperative hemoglobin reduction(8.25±5.04 vs 4.05±3.07, P < 0.05) and longer hospital stay(5.16±1.23 vs 4.05±3.07 d, P < 0.05) when compared with the FURS group. In terms of stone clearance rate, both the short-(90.32% vs 74.07%, P < 0.05) and long-term(95.16% vs 85.18%, P < 0.05) rates were statistically higher in the VUMP group than the FURS group. No differences were seen in the changes of procalcitonin and C-reactive protein in both groups(P>0.05). The overall complications were significantly lower in the VUMP group than the FURS group(16.12% vs 25.92%, P < 0.05), especially in the incidence rates of systemic inflammatory response syndrome, urinary sepsis, and perirenal hematoma. Conclusion VUMP and FURS are safe and effective in the treatment of 1.5~2.5 cm lower calyx calculi, but VUMP has the advantages of higher stone clearance rate, lower operation time and complication rate.